Histochemical analysis of glycoconjugates in the branchial mucous cells of Apareiodon affinis (Steindachner, 1879) (Characiformes, Paradontidae) - Díaz, Alcira Ofelia (2008)
The histochemical characteristics of the mucous cells located in the gills of the fish Apareiodon affinis (Steindachner, 1879) (Characiformes, Paradontidae) were investigated. Several methods for the localization and characterization of glycoconjugates (GCs) with oxidizable vicinal diols, O -acyl sugars, O- sulphate esters and sialic acids residues without O-acyl substitution or with O-acyl substitution at C7, C8 or C9 were employed. Mucous cells were observed among the epithelial cells of the filament and the gill lamellae. No histochemical differences were detected between the mucous cells of primary and secondary lamellae. They contained high amounts of GCs with carboxyl groups and O-sulphate esters, together with moderate amounts of GCs with oxidizable vicinal diols, and low amounts of GCs with sialic acids. This work demonstrated the heterogeneity of the mucous cells GCs, which could be associated with different functions such as lubrication, protection and inhibition of the invasion and proliferation of pathogenic microorganisms and ionic regulation.